Neighborhood segregation and cancer prevention guideline adherence in US Hispanic/Latino adults: Results from the HCHS/SOL - Pichardo, Margaret S.; Pichardo, Catherine M.; Talavera, Gregory A.; Gallo, Linda C.; Castañeda, Sheila F.; Sotres-Alvarez, Daniela; Molina, Yamile; Evenson, Kelly R.; Daviglus, Martha L.; Hou, Lifang; Joyce, Brian; Aviles-Santa, Larissa; et al. (Frontiers in Oncology, 2022)
Background Adherence to the American Cancer Society (ACS) guidelines for cancer prevention is associated with a lower risk of cancer and mortality. The role of neighborhood segregation on adherence to the guidelines among Hispanic/Latino adults is relatively unexplored. Materials and methods The Hispanic Community Health Study/Study of Latinos is a community-based prospective cohort of 16,462 Hispanic/Latino adults, ages 18-74 years enrolled in 2008-2011 from the Bronx, Chicago, Miami and San Diego. Dimensions of neighborhood segregation were measured using 2010 United States’ census tracts:—evenness (the physical separation of a group), exposure (the propensity for contact between groups), and their joint effect (hypersegregation). ACS guideline adherence levels – low, moderate, high – were created from accelerometry-measured physical activity, dietary intake, alcohol intake, and body mass index. Weighted multinominal logistic regressions estimated relative risk ratios (RRR) and 95% confidence intervals (CI) for guideline adherence levels and its components. Results Hispanic/Latino adults were classified as low (13.7%), moderate (58.8%) or highly (27.5%) adherent to ACS guidelines. We found no evidence of an association between segregation and overall guideline adherence. Exposure segregation associated with lower likelihood of moderate adherence to alcohol recommendations (RRRmoderate vs. low:0.86, 95%CI:0.75-0.98) but higher likelihood for diet recommendations (RRRmoderate vs. low:1.07, 95%CI:1.01-1.14). Evenness segregation associated with lower likelihood of high adherence to the physical activity recommendations (RRRhigh vs. low:0.73, 95%CI:0.57-0.94). Hypersegregation was associated with individual guideline components. Conclusion We found evidence of a cross-sectional relationship between neighborhood segregation and ACS cancer prevention guideline components, but not with overall ACS guideline adherence.